18.3k views
2 votes
7. If f(x) = ae^-ax for a > 0, then f'(x) =

User Arek Bal
by
5.2k points

1 Answer

4 votes

Answer:


f'(x)=-a^2e^(-ax)

General Formulas and Concepts:

Calculus

  • Chain Rule:
    (d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)
  • Derivative:
    (d)/(dx) [e^u]=e^u \cdot u'

Explanation:

Step 1: Define


f(x)=ae^(-ax)

Step 2: Find Derivative

  1. Derivative eˣ [Chain Rule]:
    f'(x)=ae^(-ax) \cdot -a
  2. Condense/Simplify:
    f'(x)=-a^2e^(-ax)
User Bolek Tekielski
by
4.9k points